2012
DOI: 10.1088/0957-4484/23/45/455501
|View full text |Cite
|
Sign up to set email alerts
|

A novel methane sensor based on porous SnO2nanorods: room temperature to high temperature detection

Abstract: We report for the first time a novel room temperature methane (CH(4)) sensor fabricated using porous tin oxide (SnO(2)) nanorods as the sensing material. The porous SnO(2) nanorods were synthesized by using multiwall carbon nanotubes (MWCNTs) as templates. Current versus time curves were obtained demonstrating the room temperature sensing capabilities of the sensor system when exposed to 0.25% CH(4) in air. The sensor also exhibited a wide temperature range for different concentrations of CH(4) (25-500 °C), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…Recently, porous SnO 2 nanostructures responded even at room temperature (RT) against 1000 ppm CH 4 gas. 7 However, the mechanism of detection is not well understood.…”
Section: Sensing At Low Operating Temperaturesmentioning
confidence: 99%
“…Recently, porous SnO 2 nanostructures responded even at room temperature (RT) against 1000 ppm CH 4 gas. 7 However, the mechanism of detection is not well understood.…”
Section: Sensing At Low Operating Temperaturesmentioning
confidence: 99%
“…However, the need for highly selective, low-concentration detection has driven the research for high-performance materials. During the past decade, nanostructured materials of various morphologies such as nanowire, nanorod, nanobelt, nanoflower and hollow sphere have been investigated for gas-sensing performance [2][3][4][5][6]. The studies revealed that gas-sensing performance can be enhanced when the sensing material is in the form of nanostructure.…”
Section: Introductionmentioning
confidence: 99%
“…While many projects utilize sensors capable of detecting criteria pollutants, advances in the development of metal-oxide semiconductor (MOx) sensors have led to sensors capable of detecting methane in settings closer to ambient environmental conditions (Quaranta et al, 1999;Biaggi-Labiosa, 2012). Eugster and Kling (2012) demonstrated the ability of the Figaro 30 TGS 2600 sensor to resolve diurnal methane fluctuations in a remote area of Alaska.…”
Section: A Place For Sensorsmentioning
confidence: 99%